CORRIGENDA - Gudžinskas, Liutauras (Baltic Journal of Political Science, 2017)
In the previous issue of The Baltic Journal of Political Science (no. 4, 2015), Kamil Ławniczak, co-author of the article Poland’s International Relations Scholarly Community and its Distinguishing Features According to the 2014 TRIP Survey of International Relations Scholars, was misidentified as a “PhD student” in a footnote of page 94. Kamil Ławniczak possesses a PhD degree. We apologise to the author for this regrettable error.